An integrated new threshold FCMs Markov chain based forecasting model for analyzing the power of stock trading trend - Kavitha Ganesan; Udhayakumar Annamalai; Nagarajan Deivanayagampillai (Financial Innovation, 2019)
This paper explores the power of stock trading trend using an integrated New Threshold Fuzzy Cognitive Maps (NTFCMs) Markov chain model. This new model captures the positive as well as the negative jumps and predicts the trend for different stocks over 4 months which follow an uptrend, downtrend and a mixed trend. The mean absolute per cent error (MAPE) tolerance limits, the root mean square error (RMSE) tolerance limits are determined for various stock indices over a multi-timeframe period and observed for the existing methods lying within the defined limits. The results show for every "n" number of predictions made, the predicted close value of the day's stock price was within tolerance limit with 0 % error and with 100% accuracy in predicting the future trend.
Keywords: 650; Financial markets; Prediction intervals; Price forecasting; Comparative studies; Decision making; Fuzzy cognitive maps (FCMs); Markov chain